Pengaruh Pelayanan, Promosi, Dan Motivasi Terhadap Kinerja Karyawan PT.PLN (Persero) ULP Medan Baru - Widia Natalia Daeli; Deni Faisal Mirza; Muhammad Fadlan; Purjianto Purjianto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study discusses the influence of Service, Promotion, and Motivation on the performance of employees of PT PLN (PERSERO) ULP MEDAN BARU. The theory used in the study is marketing management theory. The research method used by research is a quantitative approach. The type of research is descriptive quantitative. The research population of all employees of PT PLN (PERSERO) ULP MEDAN BARU was 22 people and the sample of this study was taken with saturated sampling technique saturated sampling technique if the sample and population members are relatively small, less than 30 people, or researchers who want to make generalizations with very small errors. Another term for saturated sampling is census, where all members of the population are sampled using the slovin formula, namely 22 respondents. Data collection in this study was by means of questionnaires, interviews, documentation. The data were analyzed using multiple linear analysis models. The results showed that the X1 tcount value was 0.277 < t table 2.086 with a significant 0.785> 0.05, so Ha was rejected and Ho was accepted, indicating that X1 had no positive and insignificant effect on Y, X2 tcount value of 2. 102 > t table 2,086 with a significant 0.050 < 0.05 then Ho is rejected and Ha is accepted indicating that X2 has a positive and significant effect on Y, X3 tcount value of 4,281 > t table 2,086 with a significant 0.000 < 0.05 then Ho is rejected and Ha is accepted indicating that X3 has a positive and significant effect on Y.